THE EFFECT OF ORGANIZATIONAL COMMITMENT ON SERVICE EXCELLENT AT PALM CAFÉ - Daria Aryutami M. Selasa; Juliana Juliana (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The development of the hotel business, which is running more rapidly, and the recovery of the tourism industry also has an impact on the food and beverage provider sector which continues to grow. Doing business in providing food and drinks what is offered to guests is not only about food and drinks, but also the quality of service provided to guests. This study aims to analyze the relationship of organizational commitment to service excellent using quantitative research methods and collecting interview data and direct observation which clearly describes the object under study. Data analysis method used linear regression analysis with the help of Partial Least Square -SEM consists of two variables The target population in this study was all employees in palm café and the sample in this study was employees who worked in the food and beverage Service Department which amounted to 16 research respondents using the non-probability sampling method. Nonprobability sampling is a sampling technique Organizational Commitment as an independent variable and Service Excellent as the dependent variable. Employee commitment formed through regular employee training is one approach that has been used by organizational companies to achieve company goals in increasing profits. Employees who are trained continuously will have extensive knowledge, skills, and insights that will improve their job performance through the quality of service provided to customers by providing service excellent and besides that will generate loyalty to the company. In this study, employee organizational commitment has a relationship with service excellent.